Wireless vibration monitoring system (WVMS) - Wong Yoon Khang (Universiti Malaysia Perlis, 2008)
The purpose of developing this project is to monitor the vibration naturally through wireless. The idea of this project is to make the data transfer wireless between sensor and PC, based on the RF technology. Generally a set of system design requirements are developed that cover 3 main parts, which consists of the hardware module transmitter and receiver which is the RF wireless data transfer, the design of the vibration sensor circuit to detect vibration surroundings within certain ranges, and software for the monitoring capabilities for vibroseis data access and management. RF wireless technology was chosen to implement the wireless module for its low cost, low power and its ability to be incorporated into small control board. Besides that, Personal Computer (PC) can be an extremely useful tool for data acquisition and control because it enables the collection of sensory information as well as the control of systems. A practical vibration detector using typical vibration sensor is used to trace the vibration signal that is within the operation range and the transmitter is used for the transmission. PC will receive the digital signal from Analogue Digital Converter (ADC) through the receiver that will receive the entire signal. At the software interface, Visual Basic software is used for monitoring system purpose which can display all the critical vibroseis data in binary digit in line graph and numeric views of data at sample rates per second. The vibration signal detected from the sensor is very sensitive to the disturbance surroundings. The problem can be solved by using Microcontroller to realize the transmission of the vibroseis signal more effectively.